If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -1(3x + -4) = 8 + -6x + -6 + 5x Reorder the terms: 7x + -1(-4 + 3x) = 8 + -6x + -6 + 5x 7x + (-4 * -1 + 3x * -1) = 8 + -6x + -6 + 5x 7x + (4 + -3x) = 8 + -6x + -6 + 5x Reorder the terms: 4 + 7x + -3x = 8 + -6x + -6 + 5x Combine like terms: 7x + -3x = 4x 4 + 4x = 8 + -6x + -6 + 5x Reorder the terms: 4 + 4x = 8 + -6 + -6x + 5x Combine like terms: 8 + -6 = 2 4 + 4x = 2 + -6x + 5x Combine like terms: -6x + 5x = -1x 4 + 4x = 2 + -1x Solving 4 + 4x = 2 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 4 + 4x + x = 2 + -1x + x Combine like terms: 4x + x = 5x 4 + 5x = 2 + -1x + x Combine like terms: -1x + x = 0 4 + 5x = 2 + 0 4 + 5x = 2 Add '-4' to each side of the equation. 4 + -4 + 5x = 2 + -4 Combine like terms: 4 + -4 = 0 0 + 5x = 2 + -4 5x = 2 + -4 Combine like terms: 2 + -4 = -2 5x = -2 Divide each side by '5'. x = -0.4 Simplifying x = -0.4
| log(7)=2 | | 14.40+4.05p=4.50(3+p) | | y=13x+404+46 | | 3(3x-6)=1-2x | | x+(x-10)+2(x-10)+6=100 | | 3x^2-5xy+2y^2+3x=0 | | 2.8-5.6= | | 5y-30y+10=-52+2y-4y | | (x^2+x)-6= | | 5*24-3x=90 | | 3k-s=7k-21 | | 5(y+2)=4-7 | | =y-6y^3 | | -(x-1)-3(x+4)=x | | -(x-1)+3(x+4)=x | | 16x+12x=100 | | xy+2x-3y+2+12(x^2)y-3x(y^2)-12x+18y=16 | | 2(x-1)=-(x-3)+(4-x) | | -5.99+23.105x=-587.72x-54.936 | | 36-yi=4x+3i | | (x+2)=-(x-3) | | 5y=11x+6 | | f(x)=2x+3x-1 | | x^2-4x=x(7+x) | | -(x+2)=-(x-3) | | 12m^2-17m-5= | | 15-4x+16=11 | | -6x+15=18x-7 | | 0=-r+6 | | 0=[r+6] | | -(3x+1)=-5 | | a^2-4a+1=0 |